Importing Democracy: The Role of NGO's in South Africa, Tajikistan, & Argentina - Fisher, Julie; EMacDesign; LLC (Kettering Foundation Press, 2013)
While street protesters demanding democratic reforms make headlines in the international news, Importing Democracy: The Role of NGOs in Sout h Africa, Tajikistan, and Argentina, written by Julie Fisher and publi shed by the Kettering Foundation Press, focuses on a quieter movement led by democratization NGOs. In South Africa, the Good Governance Lear ning Network shares participatory tools to make local governments more responsive. In Tajikistan, Jahan teaches local police about human rig hts. In Argentina, seven democratization NGOs sponsor public deliberat ions in local communities and have organized a nationwide citizens net work to combat municipal government corruption. The book is organized around three chapters for each country, South Africa, Tajikistan, and Argentina. The first chapter of each country s section begins with the historical, political, and economic context and continues with a disc ussion of the general contours of civil society. The second chapter in each section deals with the role of democratization NGOs in promoting both loyal opposition and law-based civil liberties. The third chapte r focuses on their role in promoting political culture and political p articipation. Loyal opposition and law-based civil liberties help defi ne democratization at the national level, whereas changes in political culture and increased political partici-pation often occur throughout society. Follow-ing the nine country chapters, the book concludes wit h a comparative overview and implications for international policy. Fi sher, a former Kettering Foundation program officer, writes that the i dea that democracy can be exported has lost credibility in recent year s. In many countries, however, democratization NGOs are importing demo cratic ideas and recovering local democratic traditions.